2022
DOI: 10.2196/32340
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Triage Self-assessment Using a Symptom Assessment App for Walk-in Patients in the Emergency Care Setting: Observational Prospective Cross-sectional Study

Abstract: Background Increasing use of emergency departments (EDs) by patients with low urgency, combined with limited availability of medical staff, results in extended waiting times and delayed care. Technological approaches could possibly increase efficiency by providing urgency advice and symptom assessments. Objective The purpose of this study is to evaluate the safety of urgency advice provided by a symptom assessment app, Ada, in an ED. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The study by Chan et al [ 35 ] (reported earlier) showed significantly better triage accuracy by their locally developed symptom checker than the patients overall (73% vs 58%; P <.01), and performance on emergency and urgent cases was stronger than on routine or home care. A recent study on the use of Ada by 378 “walk-in” patients in urgent care compared its triage accuracy with the result of a triage nurse using the Manchester Triage System [ 44 ]. The app was shown to undertriage 8.9% of cases and overtriage 57.1%, although physician assessment of the undertriaged cases suggested that 14 cases (3.7%) did not represent a risk of an adverse event.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Chan et al [ 35 ] (reported earlier) showed significantly better triage accuracy by their locally developed symptom checker than the patients overall (73% vs 58%; P <.01), and performance on emergency and urgent cases was stronger than on routine or home care. A recent study on the use of Ada by 378 “walk-in” patients in urgent care compared its triage accuracy with the result of a triage nurse using the Manchester Triage System [ 44 ]. The app was shown to undertriage 8.9% of cases and overtriage 57.1%, although physician assessment of the undertriaged cases suggested that 14 cases (3.7%) did not represent a risk of an adverse event.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, online-symptom checkers have been studied with respect to their overall diagnostic and triage accuracy, but these have similarly been faced with challenges surrounding accuracy, and rates of over or under triage. [1416] Artificial intelligence may also have uses in triage, with machine learning models having been demonstrated as having some success with specific presenting complaints. [1719] The possibilities of how triage can evolve can take a variety of different forms, and these merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…27 Interventions have used strategies such as improving primary care access, 6 and ED diversion either before or at the time of ED visit. 28,29 In addition, there has been evidence of increasing utilization of non-ED options for receiving acute care such as urgent care centers for treatment of low-acuity conditions. 2 Identification of potentially avoidable ED visits is an important issue to consider when addressing healthcare costs and quality.…”
Section: Discussionmentioning
confidence: 99%